Altered Expression of Genes Encoding Neurotransmitter Receptors in GnRH Neurons of Proestrous Mice - Vastagh, Csaba; Rodolosse, Annie; Solymosi, Norbert; Liposits, Zsolt (Frontiers in Cellular Neuroscience, 2016)
Gonadotropin-releasing hormone (GnRH) neurons play a key role in the central regulation of reproduction. In proestrous female mice, estradiol triggers the pre-ovulatory GnRH surge, however, its impact on the expression of neurotransmitter receptor genes in GnRH neurons has not been explored yet. We hypothesized that proestrus is accompanied by substantial changes in the expression profile of genes coding for neurotransmitter receptors in GnRH neurons. We compared the transcriptome of GnRH neurons obtained from intact, proestrous and metestrous female GnRH-GFP transgenic mice, respectively. About 1500 individual GnRH neurons were sampled from both groups and their transcriptome was analyzed using microarray hybridization and real-time PCR. In this study, changes in mRNA expression of genes involved in neurotransmitter signaling were investigated. Differential gene expression was most apparent in GABA-ergic (Gabbr1, Gabra3, Gabrb3, Gabrb2, Gabrg2), glutamatergic (Gria1, Gria2, Grin1, Grin3a, Grm1, Slc17a6), cholinergic (Chrnb2, Chrm4) and dopaminergic (Drd3, Drd4), adrenergic (Adra1b, Adra2a, Adra2c), adenosinergic (Adora2a, Adora2b), glycinergic (Glra), purinergic (P2rx7) and serotonergic (Htr1b) receptors. In concert with these events, expression of genes in the signaling pathways downstream to the receptors, i.e. G-proteins (Gnai1, Gnai2, Gnas), adenylate-cyclases (Adcy3, Adcy5), protein kinase A (Prkaca, Prkacb) protein kinase C (Prkca) and certain transporters (Slc1a4, Slc17a6, Slc6a17) were also changed. The marked differences found in the expression of genes involved in neurotransmitter signaling of GnRH neurons at pro- and metestrous stages of the ovarian cycle indicate the differential contribution of these neurotransmitter systems to the induction of the pre-ovulatory GnRH surge, the known prerequisite of the subsequent hormonal cascade inducing ovulation.